The Influence of Workload on Anxiety Levels Among Private Sector Employees in East Jakarta - Churnawan, Rizky Purnomo Adji (Greenation Publisher & Yayasan Global Research National, 2025)
This study aims to examine the extent to which workload intensity contributes to anxiety levels among private sector employees in East Jakarta. A quantitative research design employing an associative-correlational approach was adopted. A total of 100 participants were selected using incidental sampling techniques. The research utilized structured questionnaires on workload and anxiety, both of which had undergone prior validity and reliability testing to ensure data accuracy. Data were analyzed using Pearson’s correlation to assess the strength and direction of the relationship between variables, along with simple linear regression to determine the magnitude of workload's influence on anxiety levels. The findings revealed a statistically significant correlation between workload and anxiety (r = 0.612, p = 0.000). Moreover, workload accounted for 37.4% of the variance in anxiety levels. These results suggest that a substantial increase in workload intensity may act as a catalyst for heightened anxiety among employees. It is anticipated that the insights gained from this research may serve as a critical reference for organizations in evaluating and improving their workload management strategies for employees.